2017
DOI: 10.3390/app7121209
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Evaluate the Aging Grades of Reclaimed Asphalt Binder

Abstract: Featured Application: The development of aging grades for reclaimed asphalt binder can be used to guide the design of RAP mixtures. Abstract:The use of reclaimed asphalt pavement (RAP) is of great significance for alleviating the problem of resource waste and land space occupation in the context of asphalt pavement. However, the use rate of RAP is still low in many countries because of limited understanding and no unified recycling guidelines, especially in terms of materials classification and aging grades. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…(3) The ESEM fibril microstructure of the heavily aged binders, such as RAP, may be heavier and denser and may need more intense irradiation to appear, as in the case of the HL8 24 h samples in this study. (4) The ESEM analysis of the laboratory contact blended binders showed that the increase in the temperature from 20 to 60 °C increases the width of the blended zone of the two binders. (5) Both the ESEM and FTIR analyses showed that the increase in silo storage time for the HL8 blended binder caused significant aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The ESEM fibril microstructure of the heavily aged binders, such as RAP, may be heavier and denser and may need more intense irradiation to appear, as in the case of the HL8 24 h samples in this study. (4) The ESEM analysis of the laboratory contact blended binders showed that the increase in the temperature from 20 to 60 °C increases the width of the blended zone of the two binders. (5) Both the ESEM and FTIR analyses showed that the increase in silo storage time for the HL8 blended binder caused significant aging.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition to the cost benefits of being able to produce new asphalt from old asphalt, there is also the advantage of reducing the carbon footprint of the construction significantly by reducing the emissions in the transportation of raw materials as well as the reduction in the extraction of virgin aggregates. 4 Additionally, this allows for the removal of a potential waste product in old asphalt pavement. 5 The binder in RAP is chemically transformed, notably as a result of oxidation, as it ages during service in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Kou et al [28] state that AHP was initially developed, making the most use of field data, laboratory results, and experts' experience, for applications in multicriteria decision-making, planning, and resource allocation, and in conflict resolution. Further discussion of the method can be found in [29,30], whereas its critique in [31][32][33], answered in [34].…”
Section: Decision-making Modelmentioning
confidence: 99%
“…Rejuvenators, due to their rich maltene constituents and high permeation ability, can re-balance the composition of aged asphalt binders and have become the key material in pavement-recycling technology [1][2][3]. In recent years, many pavement materials have reached the end of their service life and have been abandoned in the city (Figure 1).…”
Section: Introductionmentioning
confidence: 99%